K‐t GRAPPA accelerated phase contrast MRI: Improved assessment of blood flow and 3‐directional myocardial motion during breath‐hold. Issue 5 (21st March 2013) - Bauer, Simon; Markl, Michael; Föll, Daniela; Russe, Maximilian; Stankovic, Zoran; Jung, Bernd
<x xml:space="preserve">Abstract</x> Purpose To evaluate spatiotemporal parallel imaging with R = 5 in comparison to conventional parallel imaging with R = 2 applied to phase contrast (PC) magnetic resonance imaging (MRI). This was motivated by the fact that scan times for PC imaging often exceed breath‐hold capabilities of patients even with standard parallel imaging using typical reduction factors of R = 2. Materials and Methods K‐t generalized autocalibrating partially parallel acquisition (GRAPPA) acquisition was validated in phantom measurements and then applied in 10 volunteer and three patient examinations. Due to the higher reduction factor compared to conventional GRAPPA, k‐t GRAPPA measurements could be performed during breath‐hold with high spatial and temporal resolution. K‐t GRAPPA scans were compared to GRAPPA acquired during free‐breathing with navigator respiration control. In addition, spatiotemporally accelerated PC imaging was acquired during free‐breathing for comparison of k‐t‐accelerated breath‐held scans. Results Substantial improvements in image quality for the breath‐hold measurements were observed. Significantly reduced peak velocities were found for the GRAPPA protocol compared to the k‐t‐accelerated breath‐hold scans for both flow (8%) and myocardial motion (up to 30%) measurements. Conclusion Spatiotemporal acceleration allows the performance of high temporal or spatial resolution PC imaging during breath‐hold while providing high image quality and robust acquisition of functional information that cannot be achieved during breath‐hold with standard techniques. J. Magn. Reson. Imaging 2013;38:1054–1062. © 2013 Wiley Periodicals, Inc.